2010
DOI: 10.1017/s0143814x10000127
|View full text |Cite
|
Sign up to set email alerts
|

Politics and Privatization: Exogenous pressures, domestic incentives and state divestiture in Latin America

Abstract: Despite a pervasive trend towards state retrenchment in Latin America since the s, there remains significant variation in the levels of privatization across the region. However, very few cross-national studies of the determinants of privatization have been conducted and we still do not truly know why states privatize. This paper examines the determinants of privatization for  Latin American states over the period  to . I contend that privatization is best conceptualized as a two-stage process inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…We contend that privatization is best modeled as a two-stage process, involving an initial decision over whether to adopt privatization or not, and if adopted as a reform measure, a subsequent decision over the scale and extent of what to divest (see also Meseguer 2004;Doyle 2010). What is more, at each stage of this process endogenous and exogenous variables will generate different incentives.…”
Section: Why Do States Privatize?mentioning
confidence: 99%
See 3 more Smart Citations
“…We contend that privatization is best modeled as a two-stage process, involving an initial decision over whether to adopt privatization or not, and if adopted as a reform measure, a subsequent decision over the scale and extent of what to divest (see also Meseguer 2004;Doyle 2010). What is more, at each stage of this process endogenous and exogenous variables will generate different incentives.…”
Section: Why Do States Privatize?mentioning
confidence: 99%
“…For developing countries, given the international context at the beginning of the 1990s, this incentive may have been exacerbated, due to the debt crisis in Latin America, and the process of market liberalization in Eastern Europe after the collapse of the Soviet Union. Emulative processes played a large role in the initiation of privatizations across Latin America (see Meseguer 2004;Doyle 2010), while peer dynamics had a significant effect on the adoption of pension privatization across Eastern Europe and Central Asia (see Brooks 2005).…”
Section: Why Do States Privatize?mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, they are not included in the set of 49 studies of presidential power that we identified. 8 For example, Doyle 2010. nineteen separate and original measures of presidential power, 9 plus a further sixteen studies that used one of these measures but both/either reported scores for a different set of countries and/or gave countries different scores from the original study.…”
Section: Existing Measures Of Presidential Powermentioning
confidence: 99%